Analisis Performa Protokol 802.11n Pada Mikrokomputer Raspberry Pi - Retno Perwita Sari; Kasyful Amron; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
The need for better infrastructure development to support human resources (HR) needs to be done. One of the important infrastructure is the information technology infrastructure in the field of telecommunication. Adequate telecommunication facilities are expected to help rural areas. One of the way is with wireless technology. Wireless technology has advantages in easy installation and cheap because it does not need a cable. Wireless technology can be implemented in the form of wireless mesh with the selection of the 802.11 as a wireless protocol because it supports multiple devices and has a wide range. It is also necessary routing protocol in this research that is OLSR. OLSR to be selected due to the OLSR work concept that always updates the routing table at any times. Choosing Raspberry Pi for microcomputer due to wifi requirement that must be available that can not be given by microcontroller like arduino. Once a facility is established, a performance test is required to determine the performance of the protocol and the microcomputer used in accordance with the field conditions. Parameters in the performance testing protocol 802.11 and Raspberry Pi is packet loss, delay, throughput, CPU and memory usages. From the test results showed that the highest packet loss reached 0.38% when the measured data is the largest data in this study that is 65507 B. Highest delay reached 1.09 second while the experiment with a large data 32768 B, the largest throughput reached 64.13 Bps on the largest data is 65507 B, CPU usage is only 0,5% and memory that not exceed than 0,8% of total CPU resources available.